Effects of help options in a multimedia listening environment on L2 vocabulary acquisition. Issue 7 (2nd October 2016) - Mohsen, Mohammed Ali
ABSTRACT: Several types of help options have been incorporated into reading and listening comprehension activities to aid second language (L2) vocabulary acquisition. Textbook authors, teachers, and sometimes even students may pick and choose which help options they wish to use. In this paper, I investigate the effects of two help options in a multimedia listening environment (annotated captioned animation versus annotated transcript animation) on L2 vocabulary acquisition. Thirty-four Arab learners of English as a foreign language watched and listened to an animated story under any one of the following conditions: (1) annotations + captions + animation (ACA) and (2) annotations + transcripts+ animation (ATA). After viewing the story, the participants received a vocabulary posttest (i.e., L2 spelling) and posttest of translating Arabic words into the target language (L2 form recall). These tests were readministered five weeks after the treatment. The results revealed that the ACA and ATA groups performed significantly better on both L2 vocabulary spelling and L2 vocabulary recall in posttest and delayed test treatments than on L2 vocabulary spelling and recall in the pretest treatments. No significant difference was observed between the ACA and ATA groups in terms of vocabulary posttests. However, the ACA group slightly outscored the ATA group in the long-term L2 form recall tests (i.e., delayed tests). The results suggest that both types (i.e., ACA and ATA) help improve L2 vocabulary acquisition, whereas ACA surpasses ATA in aiding L2 vocabulary acquisition over a long term. In light of these findings, pedagogical implications to teachers, learners, and curricula designers are discussed.